2006
DOI: 10.1021/jp061962g
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Surface-Enhanced IR Absorption Spectroscopy on CO Adducts of Iron Protoporphyrin IX Self-Assembled on a Au Electrode

Abstract: The surface coordination chemistry of carbon monoxide with the reduced form (Fe(II)PP) of iron(III) protoporphyrin IX (Fe(III)PP) monolayer self-assembled on a Au electrode in 0.1 M HClO4 was studied for the first time by using in situ ATR-surface-enhanced infrared absorption spectroscopy (ATR-SEIRAS). Both mono- and biscarbonyl adducts [simplified as Fe(II)(CO)PP and Fe(II)(CO)2PP, respectively] were detected, depending on the history of potential control. Initially, the Fe(II)(CO)PP predominates, and the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Other studies show that the optical and electrical properties of conjugated macrocycle thin lms are extremely sensitive to adsorption of gas molecules (NO 2 , SO 2 , and CO 2 ), making them promising candidates for gas sensor applications [16][17][18][19][20][21] Among various strategies for the formation of macrocycle lms required for the design of these molecular devices, the leading advantage of self-assembly method is the covalent bonding between the molecules and the surface, which replaces weak van der Waals or hydrogen bonding as in the case of Langmuir-Blodgett lms. Therefore self-assembled thin lms offer very good chemical and physical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show that the optical and electrical properties of conjugated macrocycle thin lms are extremely sensitive to adsorption of gas molecules (NO 2 , SO 2 , and CO 2 ), making them promising candidates for gas sensor applications [16][17][18][19][20][21] Among various strategies for the formation of macrocycle lms required for the design of these molecular devices, the leading advantage of self-assembly method is the covalent bonding between the molecules and the surface, which replaces weak van der Waals or hydrogen bonding as in the case of Langmuir-Blodgett lms. Therefore self-assembled thin lms offer very good chemical and physical stability.…”
Section: Introductionmentioning
confidence: 99%
“…The dramatic change in the Stark effect slope of CN − at ca −0.6 V indicated a subtle orientation change. In addition, studies on CO via in situ ATR-surface-enhanced infrared absorption spectroscopy were performed by Cai [12] and surface-enhanced IR spectroscopy by Osawa. [13] They deduced the molecular orientation on the basis of the electrochemical Stark effect and surface selection rules.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that both CO and NO x can not bind to the active site of FeN x /C catalyst (Figure d). It has been reported that CO can bind to Fe II porphyrins but can not to Fe III porphyrins . The insensitivity of P m PDA-FeN x /C to CO and NO x suggests that Fe valence state may be Fe III if active site contains iron atom.…”
mentioning
confidence: 99%
“…It has been reported that CO can bind to Fe II porphyrins but can not to Fe III porphyrins. 19 The insensitivity of PmPDA-FeN x /C to CO and NO x suggests that Fe valence state may be Fe III if active site contains iron atom.…”
mentioning
confidence: 99%